Effect of preconception multiple micronutrients vs. iron–folic acid supplementation on maternal and birth outcomes among women from developing countries: a systematic review and meta-analysis - Das, Rashmi Ranjan; Sankar, Jhuma; Jaiswal, Nishant; Dwibedi, Bhagirathi; Satapathy, Amit Kumar; Pradhan, Pranita; Sahu, Prajyoti (Frontiers in Nutrition, 2024)
Background: Maternal malnutrition affects somatic growth of the foetus and subsequent adverse events during infancy and childhood period. Though trials have been conducted on multiple micronutrient (MMN) supplements initiated during pre-conception period, there is no collated evidence on this.Recommendations Assessment, Development and Evaluation (GRADE). The searches were conducted till 30 th September 2023. Review Manager 5 software to do the meta-analysis. Primary objective was to compare the effect of pre-conception MMN vs iron folic acid (IFA) supplementation on newborn anthropometric parameters at birth.Of 11832 total citations retrieved, 12 studies with data of 11,391 participants [Intervention = 5767; Control = 5624] were included. For the primary outcome, there was no significant difference in the birth weight [MD, 35.61 (95% CI,.83 to 79.06), p = 0.11], birth length [MD, 0.19 (95% CI, -0.03 to 0.42), p = 0.09], and head circumference [MD, -0.25 (95% CI, -0.64 to -0.14), p = 0.22] between the MMN and control group. For all the secondary outcomes [except for small for gestational age (SGA), and low-birth weight (LBW)], the difference between MMN and control group was not significant. The GRADE evidence generated for all the outcomes varied from "very-low to moderate certainty".A "very-low certainty" of evidence suggests that MMN supplementation may not be better than routine IFA supplementation in improving newborn anthropometric parameters (weight, length, and head circumference). The adverse events resulting from the supplementation were not significant. We need better quality uniformly designed RCTs before any firm recommendation can be made.